Liquidity and leverage - Adrian, Tobias; Shin, Hyun Song (Journal of Financial Intermediation, 2010)
In a financial system in which balance sheets are continuously marked to market, asset price changes appear immediately as changes in net worth, and eliciting responses from financial intermediaries who adjust the size of their balance sheets. We document evidence that marked-to-market leverage is strongly procyclical. Such behavior has aggregate consequences. Changes in dealer repos – the primary margin of adjustment for the aggregate balance sheets of intermediaries – forecast changes in financial market risk as measured by the innovations in the Chicago Board Options Exchange Volatility Index VIX index. Aggregate liquidity can be seen as the rate of change of the aggregate balance sheet of the financial intermediaries.